Adenium Obesum (Forsk.) (Apocynaceae) - A New Larval Host Plant of The Common Indian Crow Euploea Core (Cramer) (Lepidoptera: Nymphalidae) - Das, Rudra Prasad; Manna, Sikas Subhra; Das, Somnath Pal; Roy, Arjan Basu (Journal of the Bombay Natural History Society (JBNHS), 2012)
No Abstract.